2021
DOI: 10.3389/fpls.2021.627315
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification Reveals That Nicotiana benthamiana Hypersensitive Response (HR)-Like Lesion Inducing Protein 4 (NbHRLI4) Mediates Cell Death and Salicylic Acid-Dependent Defense Responses to Turnip Mosaic Virus

Abstract: Hypersensitive response (HR)-like cell death is an important mechanism that mediates the plant response to pathogens. In our previous study, we reported that NbHIR3s regulate HR-like cell death and basal immunity. However, the host genes involved in HR have rarely been studied. Here, we used transcriptome sequencing to identify Niben101Scf02063g02012.1, an HR-like lesion inducing protein (HRLI) in Nicotiana benthamiana that was significantly reduced by turnip mosaic virus (TuMV). HRLIs are uncharacterized prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…p and HRLI: Potri.010G073400.1. p) (Lv et al, 2017;Wu et al, 2021). These proteins increased in abundance in BESC-22 within 24 hpi and decreased in abundance in BESC-801 across all timepoints (Figure 5).…”
Section: Systemic Acquired Resistance and Hypersensitive Response Pro...mentioning
confidence: 92%
See 1 more Smart Citation
“…p and HRLI: Potri.010G073400.1. p) (Lv et al, 2017;Wu et al, 2021). These proteins increased in abundance in BESC-22 within 24 hpi and decreased in abundance in BESC-801 across all timepoints (Figure 5).…”
Section: Systemic Acquired Resistance and Hypersensitive Response Pro...mentioning
confidence: 92%
“…Arabidopsis are induced by PTI and may act as membrane scaffolds for other defense-response proteins (Lv et al, 2017). HRLI proteins mediate cell death and are involved with SA defense signaling (Wu et al, 2021). As such, it is likely that the P. trichocarpa-S. musiva interaction begins with pathogen recognition that subsequently leads to PTI and SAR, which in turn primes adjacent plant cells for defense and HR.…”
Section: Systemic Acquired Resistance Is Elicited By Besc-22 During T...mentioning
confidence: 99%
“…In a recent report, we analysed the transcriptomics data of TuMV‐infected N. benthamiana (Wu et al., 2021). From the differentially expressed genes, we identified that the transcript level of NbeIF6 markedly increased in TuMV‐infected plants.…”
Section: Resultsmentioning
confidence: 99%
“…Dof proteins are involved in various biological processes, including but not limited to endosperm development, plant defense, seed germination, gibberellin response and auxin response ( Yu et al., 2019 ). AP2/ERF proteins play vital roles in regulating plant growth and development and various abiotic stress response ( Wu et al., 2021 ). It has noticed that BnLORs were mainly regulated by these TFs, further supporting the prediction that BnLORs perform crucial functions in the regulation of abiotic stresses and hormone treatments.…”
Section: Resultsmentioning
confidence: 99%